Evaluation Of The Antiherpetic Activity Of Licorice Root Extract In The Treatment Of Herpetic Stomatitis In Pregnant Women - Yuldasheva, Nasiba; Komilova, Adiba (Journal of Neonatal Surgery, 2025)
The purpose of this study was to evaluate the antiherpetic activity of licorice root in the treatment of herpetic stomatitis in pregnant women. 76 pregnant women were examined, 58 of whom had herpetic stomatitis. The activity of cytokine IL-10 in the oral fluid and the activity of ceruloplasmin, IAP -1 and TAP in the blood were studied. Against the background of licorice root use, an increase in the level of IL-10 in the oral fluid and blood serum, a decrease in the level of ceruloplasmin, IAP and TAP was noted in pregnant women with herpetic stomatitis.